Response to sowing dates and performance of different sunflower (Helianthus annuus) hybrids during rainy season in high-intensity cropping systems - SUR, H S; SHARMA, A R (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted for 3-years during 1995-97 on the feasibility of growing sunflower (Helianthus annuus L.) during rainy season (August-November) in the Shiwalik foothills of Punjab at Ballowal Saunkhri. ’Jawalamukhi’ sunflower hybrid was sown on varying dates, viz 4-6 August, 11-13 August,Â 18-20 August and 25-29 August in different years. In another trial in 1997, different hybrids, viz ’PSFH 67’. ’GK 2002’, ’SH 3322’, ’MSFH 8’, ’PSH 17’ and ’Jawalamukhi’ were evaluated when sown on 8 August. The results indicated that sunflower could be grown successfully, with seed yield ranging from 1 559-2224 kg/ha depending on the variable rainfall pattern in different years. The crop sown on 1113 August gave the highest yield of seed (1 587-2453 kg/ha) and stover (3 563-3970 kg/ha) in all the years and there was a gradual decrease in yield with delay in sowing. The crop growth duration increased from 92-99 days but the total heat units (0C) decreased from 1731 - 1621 with delay in sowing, as the late-sown crop experienced lower temperature during’ the seed-filling period. The coefficient of variation (CV%) was low for the total growth duration (2.9%) and heat units (26%) suggesting that these parameters can be reasonably well predicted under the present conditions. None of the other hybrids was superior to ’Jawalamukhi’. Fresh fodder yield of pearl millet [Pennisetlum glaucum (L.) R. Br. emend. Stuntz] grown uniformly before sunflower (July-August) ranged from 3 296.-6 429 kg/ha in 32-55 days. The performance of winter season (November-April) crops,of wheat (triticum aestivum L. emend. Fiori & Paol.), barley (Hordeum vulgare L.), oats (Avena sativa L.), lentil (Lens culinaris Medik.) and safflower (Carthamus tincorius L.) decreased with delay in sowing from 7 November to 3 December and depended greatly on the rainfall receivcd during the growth season.